Anatomical and functional fеatures of Deschampsia antarctica (Poaceae) leaf blade growing on the Argentine Islands - Kordyum, E. L.; Nedukha, O. M.; Ovcharenko, Y. V.; Jadko, S. I.; Ivanenko, G. F.; Loya, V. V. (Ukrainian Antarctic Journal, 2017)
The objective of the work was to perform the comparative studies of the anatomical structure and reactive oxygen species (ROS) content in leaves of Deschampsia antarctica plants growing in extreme climatic conditions of Antarctica (Skua and Galindez Іslands). The leaf anatomy and surface ultrastructure were investigated by the methods of light and scanning electron microscopy. To determine the localization of monolignines a cytochemical method of dyeing tissues was used. The ROS content was registered by measuring the spontaneous chemiluminescence (SCL). The obtained results showed the similarity of leaf anatomical and ultrastructural features in plants collected on Scua and Galindez Islands. The localization of two monolignines (syringyl and quaiacyl) detected in leaf cell walls was also similar in the investigated plants. Syringyl is mainly localized in the walls of epidermal cell and quaiacyl is mainly localized in the walls of mesophyll cells and vessels. In epidermal cell walls, the syringyl relative content exceeded the quaiacyl content 6-8 times. The SCL level in D. аntarctica leaves is corresponded to mean values of leaf luminescence in other species under the normal conditions. This may indicate the adaptation of species to harsh habitats. In our opinion, it should be paid special attention on the study of D. аntarctica cell metabolism and its regulation for better understanding the mechanisms of its survival in the conditions of the Maritime Antarctic.